Lieutenant Sonia Vagliano : a memoir of the World War II refugee crisis - Vagliano-Eloy, Sonia (The University Press of Kentucky, 2022)
"Hundreds of World War II memoirs have been written, but the stories about the bravery and valor of the women who also served are rarely told. In Lieutenant Sonia Vagliano: A Memoir of the World War II Refugee Crisis, Vagliano provides a gripping and compelling account of how she and her team of four French women were attached to an American First Army unit that arrived in Normandy two weeks after D Day. From 1943 to 1945, Vagliano followed her unit from Normandy to Paris, through Belgium, and finally into Germany where they cared for 20,000 displaced persons and prisoners of war each day. Rich in detail, Vagliano not only describes her experiences-from caring for thousands of refugees in the worst possible conditions, to defusing landmines, being kidnapped, shot at, torpedoed, and bombed-she also recounts the major events of the war in Europe including the liberation of Paris, the Battle of the Bulge, and, finally, the concentration camps. Spending five weeks at Buchenwald repatriating the 21,000 prisoners still there, she provides a unique witness to the transition period between the liberation of the camp and its turnover to the Russians in July 1945, and saw first-hand "to what extremes the human imagination can go in its search for the most cruel methods of torture." Striking a balance between daredevil-level escapades and the sobering reality of a war-time account, this book won the 1982 Saint Simon award for best memoir of the year under its original title Les Demoiselles de Gualle. Now translator and editor Martha Noel Evans brings the young French lieutenant's memoirs to English-speaking audiences for the first time"--